Analisis Kestabilan Model Selwr Dinamika Burnout Pada Mahasiswa - Maya Sari Syahrul; Nurweni Putri; Riolin Dwitari (GLOBAL SCIENTS PUBLISHER, 2026)
Academic burnout is a condition of physical, emotional, and mental exhaustion caused by prolonged academic pressure that may affect students’ well-being and performance. This study aims to analyse the stability of student burnout dynamics using the SELWR (Susceptible–Exposed–Light–Weight–Recovered) compartmental mathematical model as an extension of the SIR model. The model is formulated as a system of nonlinear differential equations representing the transition of students from susceptible to recovered conditions. The analysis reveals the existence of two equilibrium points, namely the burnout-free equilibrium and the endemic burnout equilibrium. Stability analysis is carried out by linearising the system using the Jacobian matrix and eigenvalue analysis around the equilibrium points.